KESETARAAN GENDER PERSPEKTIF SITI WALIDAH (NYAI AHMAD DAHLAN) TERHADAP KELUARGA ISLAM DI INDONESIA - Suryatama, Muhammad Ajiseftian (Mitsaqan Ghalizan, 2024)
In essence, humans are able to optimize their abilities in order to be independent and get a decent job, including for women. But in reality, women are still contaminated with the Patriaki culture. For example in the family, men are allowed to go to high school while women are only at a low level and in the environment. So that in the formulation of the problem how the rights and obligations of the husband and wife towards the development of the Islamic family in Indonesia? And how is the relevance of the role of Siti walidah (Nyai Ahmad Dahlan) in improving women through education at the present time? The research method used in this study is library research or library reserch, which is research that collects data and information on various materials contained in books or literature related to activities with the thoughts of Siti Walidah. The results showed that in the context of developing Islamic families through education in Indonesia, the contribution of wives in education such as wives are often more involved in the daily education of children at home, both in terms of character building and academics. The Islamic education system must be an alternative to humans to achieve the forms and aspects of humanity as a whole both physically and mentally. The relevance of the real steps of Siti Waidah or Nyai Ahmad Dahlan's thinking is that she succeeded in making a madarasah. Nyai Ahmad Dahlan initiated special classes for women, including teaching religion, life skills, and basic science. This opened up opportunities for women to get better access to education. Likewise, the organization Aisyiyah was born in 1917, a women's organization under Muhammadiyah. Aisyiyah focuses on empowering women, one of which is through education.